Psychosocial needs of patients and spouses justify a position of psychosocial health professionals in the multidisciplinary care for Parkinson's disease. (2020) - Duits, Annelien; van der Heijden, Colin; van het Hoofd, Masja; Roodbol, Gabriel; Tiemessen, Mark; Munneke, Marten; Steppe, Maxime
Abstract: Introduction: Living a life with Parkinson's Disease (PD) is a challenge for both patients and spouses. Patients have to cope with an increasing limitation in all domains of their daily life and spouses need to adjust to these changes. The focus of this study is on exploring, both quantitatively and qualitatively, the psychosocial needs of both patients with PD and spouses. Methods: An online survey with 11 themes, related to dealing with a chronic disease, was sent by an email to patients and spouses and two focus groups were planned, one with patients and one with spouses. Data from the survey were quantitatively analysed and audiotapes from the focus groups were transcribed verbatim and combined with notes. Results: Percentages of relevance are higher than 50% for all the themes, whereas those of the need for and received support are all lower than 50%. Focus groups revealed a negative image of psychosocial therapy and associations with failure, but also difficulties in signalling problems by professionals, little attention for spouses and limited access to specialized psychosocial care. Conclusion: Based on this exploration, there appears to be a threshold to ask for psychosocial support on the one hand and to find the right professional on the other hand. A permanent position for psychosocial health professionals in the multidisciplinary Parkinson teams and networks may close the gap between 'supply and demand'. Highlights: Living a life with Parkinson's Disease (PD) is a challenge for both patients and spouses Psychosocial therapy has a negative image leading to a high threshold to ask for support. The access to psychosocial professionals with expertise in PD is limited Psychosocial professions should have a permanent position in the multidisciplinary teams and networks to normalize their image and close the gap between needs and support.